Supplementation of red dragon fruit (Hylocereus polyrhizus) peels flour as a prebiotic in tilapia (Oreochromis niloticus) - Fadillah, Riska; Agustina, Agustina -; Pagoray, Henny; Saptiani, Gina; Reynalta, Ricko (Universitas Malikussaleh, 2024)
Red dragon fruit peels (Hylocereus polyrhizus) are an organic waste that has not been widely used with nutrients such as fibre, carotene, calcium phosphorus, vitamin B and vitamin C as antibacterial and antioxidant. This research was conducted to analyze the addition of red dragon fruit peel flour as a prebiotic for tilapia (Oreochromis niloticus). Fingerling of tilapia with an average size of 17.76 ± 1.35 g were reared for 30 days in an aquarium with a volume of 30 L. The fish were fed three times a day at satiation with treated feed, namely P0 0%; P1 5%; P2 10%; and P3 15% dragon peel flour kg-1 of feed. Each treatment was repeated three times. Parameters observed included the number of lactic acid bacteria in the gut of fish, growth performance, survival rate and haematological parameters. The results showed that the highest number of lactic acid bacteria at P3 was 5.38 log CFU mL-1, the absolute weight growth was 12.60 g, and the specific growth rate was 1.87% day-1. Supplementation of red dragon fruit peel flour did not affect the survival rate of tilapia, which ranged from 73.33- 80.00% and the haematological parameters showed a normal range. Based on this, red dragon fruit peel flour has the potential as a prebiotic in tilapia up to a dose of 15% kg-1 of feed.Keywords: Dragon Fruit Peels Flour; Growth Performance; Hematological Parameters; Prebiotics; Tilapia